Photovoltaic and interface state density properties of the Au/n-GaAs Schottky barrier solar cell - Soylu, Murat; Yakuphanoğlu, Fahrettin (Elsevier Science Sa, 2011)
The electrical and photovoltaic properties of the Au/n-GaAs Schottky barrier diode have been investigated. From the current-voltage characteristics, the electrical parameters such as, ideality factor and barrier height of the Au/n-GaAs diode were obtained to be 1.95 and 0.86 eV, respectively. The interface state distribution profile of the diode as a function of the bias voltage was extracted from the capacitance-voltage measurements. The interface state density D-it of the diode was found to vary from 3.0 x 10(11) eV(-1) cm(-2) at 0 V to 4.26 x 10(10) eV(-1)cm(-2) at 0.5 V. The diode shows a non-ideal current-voltage behavior with the ideality factor higher than unity due to the interfacial insulator layer and interface states. The diode under light illumination exhibits a good photovoltaic behavior. This behavior was explained in terms of minority carrier injecticn phenomenon. The photovoltaic parameters, such as open circuit voltage and short circuit current density were obtained to be 362 mV and J(sc) = 28.3 mu A/cm(2) under AM1, respectively. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Gallium arsenide; Schottky diode; Solar cells; Metal-semiconductor contacts